PREDICATION AND COMPREHENSION OF RESERVOIR PARAMETERS OF WELL TESTING USING PAN SYSTEM SIMULATOR FOR INDIVIDUAL AND MULTIPLE WELLS - A AMALESULARAN (AMALESW ARAN), DEVIN A AlP (Universiti Teknologi Petronas, 2011)
There are many softwares used to perform well test analysis, among which is Pan System. Many simulations have also been done to predicate reservoir parameters using well test analysis. This study aims to shed some light on the PREDICATION AND COMPREHENSION OF RESERVOIR PARAMETERS OF WELL TESTING USING PAN SYSTEM SIMULATOR FOR INDIVIDUAL AND MULTIPLE WELLS This study is a software simulation research which objective is to correlate pressure and time as a dependant variable in a well test analysis. This simulation will be using the Pan System Simulator which has been developed by Weatherford. The outcome of this simulation would be to demonstrate how well test analysis can be used to predicate reservoir parameters. Also, this study will demonstrate how a computer based well test analysis can be used to overcome the restrictions found on a manual well test analysis. The predicated parameters would then be used to study the effects of interfering wells on predicated parameters and also to classify and characterize the reservoir further. This document is a dissertation report which encompasses a background of the study, a problem statement, the objectives and scope of study, the relevancy and feasibility of study within the scope and time frame, the outline of the research methodology, the equipment involved, a Gantt chart depicting the study planning, the results obtained, discussion, conclusion and recommendation. The experiment was conducted on 7 individual wells where traditional and simulated well testing methods were conducted and also on 6 different cases of multiple well testing. Here, the results have helped comprehend the type of reservoir we are dealing with and what the parameters show. The reservoir dealt with follows a dual porosity flow regime reservoir and mostly parallel and single faulted boundaries. The criteria's of this reservoir together with the predicated parameters have aided in the understanding of the reservoir.